2016
DOI: 10.1007/s00158-016-1476-4
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective optimization for the geometry of trapezoidal corrugated morphing skins

Abstract: Morphing concepts have great importance for the design of future aircraft as they provide the opportunity for the aircraft to adapt their shape in flight so as to always match the optimal configuration. This enables the aircraft to have a better performance, such as reducing fuel consumption, toxic emissions and noise pollution or increasing the maneuverability of the aircraft. However the requirements of morphing aircraft are conflicting from the structural perspective. For instance the design of a morphing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…For the current work a Pareto based GA technique known as 'gaoptimset', was chosen in MATLAB to solve the optimisation problem. According to paper by Dayyani, Friswell [17] all settings for the optimisation were set as default except only two: the crossover function, which was set to 0.3, and the population size, set to 200. Since GA randomly generates the initial population set of individuals [18], for the identical setting parameters the optimised shape was too different.…”
Section: Genetic Algorithm Methodsmentioning
confidence: 99%
“…For the current work a Pareto based GA technique known as 'gaoptimset', was chosen in MATLAB to solve the optimisation problem. According to paper by Dayyani, Friswell [17] all settings for the optimisation were set as default except only two: the crossover function, which was set to 0.3, and the population size, set to 200. Since GA randomly generates the initial population set of individuals [18], for the identical setting parameters the optimised shape was too different.…”
Section: Genetic Algorithm Methodsmentioning
confidence: 99%
“…There are limited studies available on mechanisms for maximising strain range with constant ZPR behaviour. Adjusting the deformation mechanism can improve and potentially extends the range of ZPR deformations that a metamaterial has due to the inherent unit cell architecture [25]. However, the methodologies used for large strain NPR may be applied to ZPR metamaterials.…”
Section: Maximising the Strain Range Of Poisson Ratio Mechanical Meta...mentioning
confidence: 99%
“…Dayyani et al [35] suggested and investigated a wing design with skins made from trapezoidal cores coated with elastomeric skins. Dayyani and Friswell [36] considered static as well as aerodynamic aspects within their multi-objective optimization for the geometry of trapezoidal corrugated morphing skins. Filipovic and Kress [16] suggested a corrugation design and manufacturing method for corrugated laminates with a circular-sections corrugation shape and added scales for an aerodynamically smooth surface.…”
Section: Flexible Skin In Morphing-wing Designmentioning
confidence: 99%